Oral manifestations in chronic neutropenia in adults : a case report - Farina, Gabriela Alacarina (2018)
Chronic Neutropenia (CNP) is a primary blood disorder characterized by very low neutrophil levels every 3 to 4 weeks. Manifesting as oral ulcers, fever, lymphadenopathy, indisposition, diarrhea, and severe infections, CNP is a systemic condition that may induce the emergence of oral ulcers whose clinical aspects are sometimes mistaken for a series of other diseases. In addition, the oral manifestation of CNP may be the first event to lead a patient to look for professional healthcare. This case report describes CNP in an adult male patient with oral lesions recurring for two years and who was diagnosed by his dentist.